Long-term pamidronate treatment of advanced multiple myeloma patients reduces skeletal events - Berenson, J.R.; Lichtenstein, A.; Porter, L.; Dimopoulos, M.A.; Bordoni, R.; George, S.; Lipton, A.; Keller, A.; Ballester, O.; Kovacs, M.; Blacklock, H.; Bell, R.; et al. (Journal of Clinical Oncology, 1998)
Purpose: To determine the efficacy and safety of 21 monthly cycles of pamidronate therapy in patients with advanced multiple myeloma. Patients and Methods: Patients with stage III myeloma and at least one lyric lesion received either placebo or pamidronate 90 mg intravenously administered as a 4-hour infusion monthly for 21 cycles. At study entry, the patients were stratified according to whether they were to receive first-line (stratum 1) or second-line (stratum 2) antimyeloma chemotherapy. Skeletal events (pathologic fracture, radiation or surgery to bone, and spinal cord compression) and hypercalcemia were assessed monthly. Results: The results of the first nine previously reported cycles are extended to 21 cycles. Of the 392 randomized patients, efficacy could be evaluated in 198 who received pamidronate and 179 who received placebo. After 21 cycles, the proportion of patients who developed any skeletal event was lower in the pamidronate-group (P= .015). The mean number of skeletal events per year was less in the pamidronate-group (1.3) than in placebo-treated patients (2.2; P = .008). Although survival was not different between the pamidronate-treated group and placebo patients overall, stratum 2 patients who received pamidronate lived longer than those who received placebo (14 v 21 months, P = .041). Pamidronate was safe and well tolerated during the 21 cycles of therapy. Conclusion: Long-term monthly infusions of pamidronate as an adjunct to chemotherapy are superior to chemotherapy alone in reducing skeletal events in stage III multiple myeloma patients, and may improve the survival of patients on salvage therapy.